2019
DOI: 10.1021/acs.jpcc.9b10567
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer between CNT Surface and −Re(CO)3(phen)+* Pendants Grafted to P4VP in Nanohybrid Shish-Kebob-like Structures

Abstract: The adsorption of a Re­(CO)3(phen)-poly­(4-vinylpyridine) polymer, RePVP, on multiwall carbon nanotubes surfaces is studied by transmission electron microscopy and absorption spectroscopy in combination with chemometric techniques in MeOH/H2O solvent mixture. Nanohybrid structures like a shish-kebab (NHSK) are observed by TEM when RePVP is wrapped around carbon nanotubes (CNTs) surfaces. The association between RePVP and CNTs studied by absorption spectroscopy suggests the coexistence of CNTs with a high or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The indexes i , n , and j denote the samples, absorbing factors, and recorded wavelengths, respectively. 41 To perform the MCR-ALS analysis, we took into account the non-negative absorption spectra and non-negative concentration constraints. It was necessary to consider three independent factors ( n = 3) to accurately replicate all of the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…The indexes i , n , and j denote the samples, absorbing factors, and recorded wavelengths, respectively. 41 To perform the MCR-ALS analysis, we took into account the non-negative absorption spectra and non-negative concentration constraints. It was necessary to consider three independent factors ( n = 3) to accurately replicate all of the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, such triplet emitters can also be implemented as oxygen sensors, as their excited-state lifetime and luminescence intensity are quenched by diffusion-controlled Dexter-like energy transfer to triplet molecular dioxygen ( 3 O 2 ); in turn, singlet oxygen can be photogenerated, which is used in photodynamic therapy. Recently, we have shown that both PtCx [34,35,38] and Re(I) [39] complex can potentially perform as oxygen sensors and luminescent labels for biomedical applications.…”
Section: Thermal Decomposition In Organic Phasesmentioning
confidence: 99%